Propriedades tecnológicas de espécies florestais de pequeno diâmetro manejadas na Amazônia - Nascimento, Cristiano Souza do (Ciências de Florestas Tropicais - CFT, 2022)
The search for tropical woods with consolidated and intense use can lead to the overexploitation of native species, reducing their stock in the forest. For this reason, the indication of new species must be based on scientific information, and knowledge of the technological properties of small-diameter species is important to subsidize sustainable management of the Amazon. The objective of this thesis was to evaluate the physical, mechanical and chemical properties of forest species in a managed area in the Amazon using traditional and non-destructive methodologies to indicate rational use. The species breu-vermelho (Protium puncticulatum J.F. Macbr and P. tenuifolium Engl.), ingá (Inga alba (Sw.) Willd. and I. paraensis Ducke), mata-matá (Eschweilera coriacea DC. Mart. Ex. Berg., E. odora Poepp. and E. truncata A.C.Sm.), muirajibóia (Swartzia recurva Poepp.), murici (Byrsonima crispa A. Juss) and piãozinho (Micrandropsis scleroxylon W. Rod.) with a diameter between 25-50 cm were collected in the secondary forest area of the ZF-2 (EEST/INPA), located at the edge of km 934 on BR-174 (Manaus – Boa Vista/Brazil). In this material, the chemical properties (extractives, total polyphenols, solubility in water, lignin, cellulose, and ash), physical-mechanical (moisture, higher calorific value - PCS, basic density - Db, modulus of elasticity - MOE, and rupture - MOR), and phytochemical tests in extractives. Spectra in the near infrared region (NIR) were obtained and predictive models (non-destructive methodology) were developed and tested. In the first part of the work, the results of the chemical analyzes indicated a low concentration of ash in the studied woods, and in E. odora a high content of extractives, while in M. scleroxylon a high concentration of lignin. As for the physical-mechanical properties, the wood presents a medium to high density profile, while M. scleroxylon had higher mechanical resistance in the study. The multivariate analysis using the K-means algorithm indicated the formation of six classes for the evaluated woods, where E. truncata was grouped by the characters MOE, MOR, and ash, while I. alba by the values of cellulose, Db, MOE, and MOR. In the validation of non-destructive models (NIR) for matá-matá wood, the predicted values for the chemical and physico-mechanical properties of the woods were compatible with the destructive determinations of tropical species. In the part of the phytochemical profile of the extractives of the studied species, E. odora and E. coriacea were considered species rich in chemical classes. Tannins were the chemical class present in the extracts of the ten species. The presence of alkaloids, anthraquinones, and tannins in extractives is related to the high natural biological resistance of the species. For M. scleroxylon extractives, the phytochemical profile was composed of anthraquinones, steroids, flavonoids, and condensed tannins, emphasizing that these results are recorded for the first time. In the last part of this thesis, NIR models were tested to discriminate types of tannins in Amazonian forest species. NIR spectroscopy combined with multivariate analysis proved to be efficient (over 90% hits) and detected condensed tannins in 66% of the species. The technological characterization of small-diameter wood from a managed area in the Amazon using traditional and non-destructive methodology is a satisfactory resource for decision-making in forest management plans that may indicate the use of new species in the forestry sector.
Keywords: Madeiras de pequeno diametro